Services marketing concepts, strategies & cases - Hoffman, K. Douglas; Bateson, John E. G. (Cengage Learning, 2017)
Examine the use of services marketing as a competitive tool from a uniquely broad perspective with SERVICES MARKETING: CONCEPTS, STRATEGIES, AND CASES, 5E. Using a reader-friendly, streamlined structure, this book explores services marketing not only as an essential focus for service firms, but also as a competitive advantage for companies that market tangible products. Real examples feature businesses from industries both within and beyond the nine service economy supersectors: education and health services, financial activities, government, information, leisure and hospitality, professional and business services, transportation and utilities, wholesale and retail trade, and "other services." Cutting-edge data addresses current issues, such as sustainability, technology, and the global market, give you valuable insights for business success. A new online format additional features and flexibility to keep you up to date with the latest advances.